Books and Monographs Received (Review of Economic Studies, 1938)
Journal Article Books and Monographs Received Get access The Review of Economic Studies, Volume 5, Issue 3, June 1938, Pages 238–240, https://doi.org/10.1093/restud/5.3.238 Published: 01 June 1938